Chloroquine Inhibits Dengue Virus Type 2 Replication in Vero Cells but Not in C6/36 Cells - Kleber Juvenal Silva Farias; Paula Renata Lima Machado; Benedito Antônio Lopes da Fonseca (The Scientific World Journal)
Dengue viruses are the most important arthropod-borne viruses in terms of morbidity and mortality in the world. Since there is no dengue vaccine available for human use, we have set out to investigate the use of chloroquine as an antiviral drug against dengue. Chloroquine, an amine acidotropic drug known to affect intracellular exocytic pathways by increasing endosomal pH, was used in the in vitro treatment of Vero and C6/36 cells infected with dengue virus type 2 (DENV-2). Real-time RT-PCR and plaque assays were used to quantify the DENV-2 load in infected Vero and C6/36 cells after chloroquine treatment. Our results showed that a dose of 50 μg/ml of chloroquine was not toxic to the cells and induced a statistically significant inhibition of virus production in infected Vero cells when compared to untreated cells. In C6/36 cells, chloroquine does not induce a statistically significant difference in viral replication when compared to untreated cells, showing that this virus uses an unlikely pathway of penetration in these cells, and results were also confirmed by the plaque assay (PFU). These data suggest that the inhibition of virus infection induced by chloroquine is due to interference with acidic vesicles in mammalian cells.